2012
DOI: 10.1371/journal.pone.0037267
|View full text |Cite
|
Sign up to set email alerts
|

In vivo Ultrasound and Photoacoustic Monitoring of Mesenchymal Stem Cells Labeled with Gold Nanotracers

Abstract: Longitudinal monitoring of cells is required in order to understand the role of delivered stem cells in therapeutic neovascularization. However, there is not an imaging technique that is capable of quantitative, longitudinal assessment of stem cell behaviors with high spatial resolution and sufficient penetration depth. In this study, in vivo and in vitro experiments were performed to demonstrate the efficacy of ultrasound-guided photoacoustic (US/PA) imaging to monitor mesenchymal stem cells (MSCs) labeled wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
187
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 163 publications
(191 citation statements)
references
References 30 publications
3
187
0
1
Order By: Relevance
“…115,116 Linear ultrasound array-based PA imaging is capable of detecting a target at deeper regions than PA microscopy and thus can be applied for a rat model, having been commonly used for tissue regeneration studies. 117,118 For example, it was demonstrated that mesenchymal stem cells labeled with gold nanospheres and delivered within 96 NAM ET AL.…”
Section: Photoacoustic Imagingmentioning
confidence: 99%
See 2 more Smart Citations
“…115,116 Linear ultrasound array-based PA imaging is capable of detecting a target at deeper regions than PA microscopy and thus can be applied for a rat model, having been commonly used for tissue regeneration studies. 117,118 For example, it was demonstrated that mesenchymal stem cells labeled with gold nanospheres and delivered within 96 NAM ET AL.…”
Section: Photoacoustic Imagingmentioning
confidence: 99%
“…106,131 Therefore, fusion of ultrasonically acquired structural data and photoacoustically obtained functional and molecular data can provide synergetic benefits for a variety of applications that require noninvasive monitoring of implanted tissue-engineered constructs. 117,118 Novel dual contrast agents for combined ultrasound and PA imaging have recently been developed by indocyanine green loading to perfluorocarbon nanodroplets. 132 Also, hybrid PA imaging is possible with other optical imaging modalities, such as OCT, by sharing a photon delivery system to complement structural information.…”
Section: Multimodal Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduced viability and proliferative capability reduce the potential for translation of this particular radiotracer, since the primary goal of therapeutic stem cells is that they are effective and not that they are of definitive whereabouts. 89 Zr-oxinate 4 has also been shown to reduce cell viability by about 20% during the labelling process, although no further reduction is seen 24 hours later. It is evident that the use of a radioisotope is highly likely to affect cell function and/or toxicity.…”
Section: Positron Emission Tomography and Spect: Imaging With Radioacmentioning
confidence: 98%
“…Photoacoustic imaging has been widely reported to be capable of visualizing various biological tissues [6,7]. Compared to other ocular imaging modalities, photoacoustic imaging can achieve relatively deep penetration depth and more functional and cellular information based on photoacoustic signal generation from endogenous contrast agents such as hemoglobin and melanin [8,9].…”
Section: Introductionmentioning
confidence: 99%